Meeting report: 5th Global Forum on TB Vaccines, 20–23 February 2018, New Delhi India. (December 2018) - Atmakuri, Krishnamohan; Penn-Nicholson, Adam; Tanner, Rachel; Dockrell, Hazel M.
Abstract: The 5th Global Forum on TB Vaccines was held in New Delhi, India from 20 to 23 February 2018. This was the largest Global Forum on TB Vaccines to date with nearly 350 participants from more than 30 countries. The program included over 60 speakers in 12 special, plenary and breakout sessions and 72 posters. This Global Forum brought a great sense of momentum and excitement to the field. New vaccines are in clinical trials, new routes of delivery are being tested, novel assays and biomarker signatures are being developed, and the results from the first prevention of infection clinical trial with the H4:IC31 vaccine candidate and BCG revaccination were presented. Speakers and participants acknowledged the significant challenges that the TB vaccine R&D field continues to face - including limited funding, and the need for novel effective vaccine candidates and tools such as improved diagnostics and biomarkers to accurately predict protective efficacy. New solutions and approaches to address these challenges were discussed. The following report presents highlights from talks presented at this Global Forum. A full program, abstract book and presentations (where publicly available) from the Forum may be found attbvaccinesforum.org .